A tutorial in small molecule identification via electrospray ionization‐mass spectrometry: The practical art of structural elucidation. Issue 5 (9th November 2017) - De Vijlder, Thomas; Valkenborg, Dirk; Lemière, Filip; Romijn, Edwin P.; Laukens, Kris; Cuyckens, Filip
Abstract : The identification of unknown molecules has been one of the cornerstone applications of mass spectrometry for decades. This tutorial reviews the basics of the interpretation of electrospray ionization‐based MS and MS/MS spectra in order to identify small‐molecule analytes (typically below 2000 Da). Most of what is discussed in this tutorial also applies to other atmospheric pressure ionization methods like atmospheric pressure chemical/photoionization. We focus primarily on the fundamental steps of MS‐based structural elucidation of individual unknown compounds, rather than describing strategies for large‐scale identification in complex samples. We critically discuss topics like the detection of protonated and deprotonated ions ([M + H] + and [M − H] − ) as well as other adduct ions, the determination of the molecular formula, and provide some basic rules on the interpretation of product ion spectra. Our tutorial focuses primarily on the fundamental steps of MS‐based structural elucidation of individual unknown compounds (eg, contaminants in chemical production, pharmacological alteration of drugs), rather than describing strategies for large‐scale identification in complex samples. This tutorial also discusses strategies to obtain useful orthogonal information (UV/Vis, H/D exchange, chemical derivatization, etc) and offers an overview of the different informatics tools and approaches that can be used for structural elucidation of small molecules. It is primarily intended for beginning mass spectrometrists and researchers from other mass spectrometry sub‐disciplines that want to get acquainted with structural elucidation are interested in some practical tips and tricks.